Do Views on Sex Offending Vary by Nationality? A Comparative Analysis of Community Sentiment Toward Sex Offense Legislation in the United States and United Kingdom - Cowan, Devin (International journal of offender therapy and comparative criminology, 2021)
Much attention has been paid to the examination of community sentiment regarding convicted sex offenders and the policy that governs these offenders’ behavior. This literature, however, has largely been absent of international comparisons of sex offender community sentiment. The current study seeks to fill this gap by drawing from the results of surveys (n = 333) conducted in both the United States (US) and the United Kingdom (UK). Results indicate that sex offender policy is generally supported in both the US and the UK. Contrary to our expectations, we found that participants from the UK were less tolerant of sex offenders residing in their neighborhoods than participants from the US. Additionally, there is support for the notion that sex offender policy holds a symbolic value for both study locations. Theoretical and practical implications of these findings are discussed.